Pengembangan Wisata Tanusan Bas (Pasir Timbul) di Desa Geser, Kecamatan Seram Timur, Kabupaten Seram Bagian Timur - Fijay Kilian; Ferdinand Salomo Leuwol; Mohammad Amin Lasaiba (Jurnal Pendidikan Geografi Unpatti, 2025)
Tanusan Bas Beach (Pasir Timbul) in Geser Village, East Seram District, has great potential as a marine tourism destination. However, challenges such as limited infrastructure, inadequate facilities, and lack of promotion hinder its development. This study aims to analyze tourism potential and formulate development strategies. The research method used is descriptive qualitative with observation, interviews, and SWOT analysis. The results show that the natural beauty and biodiversity of Tanusan Bas Beach are its main attractions, but inadequate facilities hinder tourism growth. The discussion highlights the importance of adequate infrastructure, digital promotion, and community involvement in tourism management. The conclusion of this study is that with the right strategies, such as infrastructure improvement and active community participation, Tanusan Bas Beach can be developed into a leading tourism destination that contributes to the local economy and environmental conservation.